A Motherâs Struggle to Get Her Love in Vaughnâs Novel âThe Price of Everythingâ - Zuriati, Diana (STBA PRAYOGA PADANG, 2017)
AbstractThe purpose of this study was to know the reason of Giselle had to struggle to get her daughterâs love and the second reason was to know how the ways in getting her daughterâs love. In analyzing this novel, the researcher used a qualitative study using descriptive method. Based on the results of the study, the first reason that Giselle had the right to get the love of her daughter because she was the mother who gave birth to her, this happened because the pressure she got from her husband. And the second reason because she was getting pressure from her step-sister in-law who was also a lover of her husband. For this reason, Giselle tried to get her daughterâs love. The results of the second study was how the ways to get love daughterâs love, that she had to fight her step-sister in-law and how she convinced her daughter that all this were told by Alexandra about her was not true. Finally, Giselle succeeded to get her daughterâs love. This was a clear description that a mothers love for her child would never extinguish even though her child ever hurt her because a mother had a true love.Key Terms: struggle, mother, love